1998
DOI: 10.3168/jds.s0022-0302(98)75790-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time of Artificial Insemination on Pregnancy Rates, Calving Rates, Pregnancy Loss, and Gender Ratio After Synchronization of Ovulation in Lactating Dairy Cows

Abstract: In order to assess the optimal time of artificial insemination (AI) in relation to ovulation, lactating dairy cows (n = 732) from herds with rolling herd averages of 9980 to 11,800 kg from three milkings per day were randomly assigned to five groups by stage of lactation and parity. Ovulation was synchronized by administration of GnRH followed 7 d later with PGF2 alpha followed 2 d later with a second treatment with GnRH. Cows were inseminated at 0, 8, 16, 24, or 32 h after the second injection of GnRH (ovulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(36 citation statements)
references
References 37 publications
0
34
1
1
Order By: Relevance
“…The observed higher proportion of males in AI could be related to timing. Pursley et al [15] showed that in oestrus-synchronized cattle cows that inseminated early (0 hrs) and late (32 hrs) had higher proportions of producing female calves, but with less conception rates than those bred in between these times. In principle, technicians chose to carry out AI at times that ensured maximum conception rates rather than targeting proportions of male or female calves.…”
Section: Discussionmentioning
confidence: 99%
“…The observed higher proportion of males in AI could be related to timing. Pursley et al [15] showed that in oestrus-synchronized cattle cows that inseminated early (0 hrs) and late (32 hrs) had higher proportions of producing female calves, but with less conception rates than those bred in between these times. In principle, technicians chose to carry out AI at times that ensured maximum conception rates rather than targeting proportions of male or female calves.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to identify causes of repeat breeding to deal with this problem. The incidence of repeat breeding will be increased by inadequate estrous detection (Heuwieser et al, 1997;Pursley et al, 1998) resulting in errors in timing of insemination in relation to the onset of standing estrus, or insemination of cows not in estrus (Yusuf et al, 2010a). The other potential factors were also suggested, such as quality of semen and insemination technique (Hallap et al, 2006;Morrel, 2006), uterine and/or cervical/vaginal infections (Moss et al, 2002), endocrine disorders (Gustafsson, 1998;Bage et al, 2002;Lopez-Gatius et al, 2004), ovulation failures (Kimura et al, 1987;Silvia, 1994), obstructed oviducts, defective ova, anatomical defects of reproductive tract (Silvia, 1994), and early embryonic death (Gustafsson, 1998;Bage et al, 2002).…”
Section: The Incidence Of Repeat Breeding In Small Holder Dairy Farmersmentioning
confidence: 99%
“…Since this paper, many studies have evaluated the fertility of lactating dairy cows following the Ovsynch protocol, and pregnancy rates per AI have varied from 27% to 39% [11-13,15,18,19]. These pregnancy rates have been similar to [11,12] or only slightly lower [18,20] than the pregnancy rates with AI after oestrus detection or after oestrus detection following synchronisation of oestrus with PGF 2α in the control cows.…”
Section: Discussionmentioning
confidence: 99%